Cyclic Coupled Fixed Point via Interpolative Kannan Type Contractions - Abdelhafid Bassou, Youssef El Bekri, Mohamed Edraoui, Jamal Mouline (Mathematical Statistician and Engineering Applications, 2023)
In this article, we introduce the notion of cyclic coupled Kannan type contraction via interpolation. Additionally, we prove the existence a strong coupled fixed point theorem for such mappings